MODEL KEPUASAN PELANGGAN DENGAN PENGALAMAN KERJA SEBAGAI VARIABEL MODERATING - Maduretno Widowati; Mohklas . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
This research is motivated by the existence of the issue or phenomenon where there are some users of hospital services less memuasakan as the sample is; Baby missing, the alleged malpractice, patient complaints because the queues were so maximum and the lack of speed and accuracy in pasien.Hal menanganan this may indicate that the hospital services to the customers (patients) have not and or do not satisfy the customer. In general, this study aimed to analyze the effect of Service Quality, Competence and Education Level on Customer Satisfaction with Work Experience as a moderating variable. So it can be analyzed whether the variable Work experience can serve as a moderating towards Customer Satisfaction. Specifically, this research aims to increase customer satisfaction on hospital services in the city of  Semarang. With good service, competence and level of education and experience sufficient work of the hospital staff then the output will be achieved customer satisfaction.The variables in this study consisted of five variables which in the first stage variable Service Quality, Competence and Education Level becomes the independent variable while Customer Satisfaction becomes the dependent variable. Then in the second stage of the three independent variables with the variable in moderating Work Experience.Research data collection techniques by means of a questionnaire spread on hospital visitors in Semarang systematically arranged with multiple choice answers are easy to understand. Distribution of the questionnaire by means of a direct encounter conducted in the period MayAugust 2014 with a sample of some 155 people. Then the data were collected through a questionnaire to test the data analyst; validity and reliability, the classic assumption test followed by a multiple regression analysis, testing moderating variable by using MRA (Moderated RegressionAnalysis).